E-Governance in educational settings: Greek educational organizations leadership's perspectives towards social media usage for participatory decision-making. Issue 4 (30th January 2019) - Sideri, Maria; Kitsiou, Angeliki; Filippopoulou, Ariadni; Kalloniatis, Christos; Gritzalis, Stefanos
Abstract : Purpose: Even though social media are nowadays used in the frame of public governance to ensure citizens' major participation, enhance e-dialogue and e-democracy consequently, this utilization has not been expanded yet in the field of education, whose key role focuses on the cultivation of active citizenship, as it is promoted through participation. The purpose of this paper is to examine leadership's views of Greek Secondary and Tertiary Education on the potential use of social media for participatory decision-making processes in order to identify if the e-participation model could be implemented in the Greek education field as in other public domains. Design/methodology/approach: An exploratory research was elaborated, employing a survey design of quantitative method in order to explore Greek educational organizations leadership's perspectives toward social media usage in participatory decision-making processes. Findings: The research reveals Greek educational leadership's positive view on the potential effects of social media usage in participatory decision-making processes and highlights anticipated benefits as well as problems to be faced, indicating the foundation for Greek leaders to implement social media in their leadership practices and exploit their affordances as in e-governance shifts. Practical implications: Bringing the concept of e-participation and crowd sourcing model – key features in e-governance initiatives through social media usage – in education field, Greek educational leadership is informed to consider social media utilization more methodically in the context of participatory decision-making processes, updating simultaneously existing leadership practices. Originality/value: Up till now, social media usage in participatory decision-making processes in educational settings has hardly received attention.